Globalisation, economic geography and the strategy of multinational enterprises - Buckley, Peter J; Ghauri, Pervez N (Journal of International Business Studies, 2004)
The intention of this paper is to review the literature linking ownership and location strategies to economic geography and theories of globalisation and to explore new areas of research. This paper examines globalisation in terms of conflicts between markets and economic management, and suggests that the differential pace of globalisation across markets presents a number of challenges to policy makers in local, national and regional governments, and in international institutions. In examining the changing location and ownership strategies of MNEs, it shows that the increasingly sophisticated decision making of managers in MNEs is slicing the activities of firms more finely and in finding optimum locations for each closely defined activity, they are deepening the international division of labour. Ownership strategies, too, are becoming increasingly complex, leading to a control matrix that runs from wholly owned units via FDI through market relationships such as subcontracting, including joint ventures as options on subsequent decisions in a dynamic pattern. The input of lessons from economic geography is thus becoming more important in understanding the key developments in international business. The consequences of the globalisation of production and consumption represent political challenges, and reaction against these changes has led to a questioning of the effects of global capitalism as well as to its moral basis. These four issues are closely intertwined and present a formidable research agenda to which the international business research community is uniquely fitted to respond.